Intravenous myocardial contrast echocardiography predicts regional and global left ventricular remodelling after acute myocardial infarction: comparison with low dose dobutamine stress echocardiography. Issue 12 (29th March 2005) - Abe, Y; Muro, T; Sakanoue, Y; Komatsu, R; Otsuka, M; Naruko, T; Itoh, A; Yoshiyama, M; Haze, K; Yoshikawa, J
Abstract : Objective: To assess the role of intravenous myocardial contrast echocardiography (MCE) in predicting functional recovery and regional or global left ventricular (LV) remodelling after acute myocardial infarction (AMI) compared with low dose dobutamine stress echocardiography (LDSE). Methods: 21 patients with anterior AMI and successful primary angioplasty underwent MCE and LDSE during the subacute stage (2–4 weeks after AMI). Myocardial perfusion and contractile reserve were assessed in each segment (12 segment model) with MCE and LDSE. The 118 dyssynergic segments in the subacute stage were classified as recovered, unchanged, or remodelled according to wall motion at six months' follow up. Percentage increase in LV end diastolic volume (%ΔEDV) was also calculated. Results: The presence of perfusion was less accurate than the presence of contractile reserve in predicting regional recovery (55% v 81%, p < 0.0001). However, the absence of perfusion was more accurate than the absence of contractile reserve in predicting regional remodelling (83% v 48%, p < 0.0001). The number of segments without perfusion was an independent predictor of %ΔEDV, whereas the number of segments without contractile reserve was not. The area under the receiver operating characteristic curve showed that the number of segments without perfusion predicted substantial LV dilatation (%ΔEDV > 20%) more accurately than did the number of segments without contractile reserve (0.88 v 0.72). Conclusion: In successfully revascularised patients with AMI, myocardial perfusion assessed by MCE is predictive of regional and global LV remodelling rather than of functional recovery, whereas contractile reserve assessed by LDSE is predictive of functional recovery rather than of LV remodelling.